RESPON PERTUMBUHAN TANAMAN KANGKUNG (Ipomoea aquatica) TERHADAP PEMBERIAN BIOAKTIVATOR - Valentina Purnama Dewi; M. Sodik Yunadi; Sellia Virgia R; Wahyu Fajar Saputra (Agriculture Faculty of Flores University, 2021)
The purpose of this research was to examine the response of water spinach plants to the application of bioactive fermented liquid organic fertilizer on plant growth. This research used a method consisting of two treatments and one combination, namely a combination of watering and spraying treatments, as well as watering, spraying, and control. This experimen was conducted in the outdoor laboratory of SMKN 63 Jakarta, on land Kale plants. From this research, it was found that the combination of watering and spraying treatments was significantly higher and gave the best results compared to the watering, spraying, and control treatments. Based on the results of the study, it is known that there are differences in harvest age between the treatments of Watering, Spraying, Watering & Spraying and Control. The fastest harvesting age in the treatment of Watering & Spraying. Bioactive has a positive effect on vegetative growth and has a biopesticide effect. This is presumably because Bioactive is made from organic material/agricultural waste by aerobic and anaerobic fermentation methods so that from the fermentation it produces amino acids and alcohol which have an effect against plant vegetative growth and pests that often appear on crystal guava and breadfruit plants. During and after the experiment, no signs of pests or diseases were seen on the plants.